2004
DOI: 10.1111/j.0022-4367.2004.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Regret on the Demand for Insurance

Abstract: We examine optimal insurance purchase decisions of individuals that exhibit behavior consistent with Regret Theory. Our model incorporates a utility function that assigns a disutility to outcomes that are "ex post" suboptimal, and predicts that individuals with regret-theoretical preferences adjust away from the extremes of full insurance and no insurance coverage. This prediction holds for both coinsurance and deductible contracts, and can explain the frequently observed preferences for low deductibles in mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
144
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 35 publications
1
144
0
Order By: Relevance
“…Now overcompensation and a no claim rebate are equally preferred, which still seems implausible. Braun and Muermann (2004) explain low deductibles by means of regret aversion. This operates similarly to waste aversion, though the psychology is different.…”
Section: Methods A) Questionnaire Designmentioning
confidence: 99%
“…Now overcompensation and a no claim rebate are equally preferred, which still seems implausible. Braun and Muermann (2004) explain low deductibles by means of regret aversion. This operates similarly to waste aversion, though the psychology is different.…”
Section: Methods A) Questionnaire Designmentioning
confidence: 99%
“…the lowest treatment costs in case of suffering from all illnesses. This strategy is widely found in the literature and is similar to the priority heuristic (Brandstätter et al, 2006) as well as to the minimax regret theory (Savage, 1954;Braun and Muermann, 2004;Hayashi, 2008). 10 Comparing WTP values with the CE reveals that there is only a small difference for class 5.…”
mentioning
confidence: 92%
“…Again, we recall that Paroush and Venezia derived the conditions under which the optimal output in certain framework is higher than that under uncertainty in an equivalent case, although the shortage of the paper is that their results rely on the relative importance of the regret term and the firm's profits. Luckily, with the development of research, more specific and tractable regret-averse functions than that presented by Paroush and Vnezia have been proposed in many works such as in Braun and Muermann (2004), Muermann et al (2006), Mulandzi et al (2008) and so forth. Specifically, using such type of more specific and tractable regret-averse functions, Braun and Muermann (2004) examined optimal insurance purchase decisions of individuals and found that individuals with regret-theoretical preferences adjust away from the extremes of full insurance and no insurance coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Luckily, with the development of research, more specific and tractable regret-averse functions than that presented by Paroush and Vnezia have been proposed in many works such as in Braun and Muermann (2004), Muermann et al (2006), Mulandzi et al (2008) and so forth. Specifically, using such type of more specific and tractable regret-averse functions, Braun and Muermann (2004) examined optimal insurance purchase decisions of individuals and found that individuals with regret-theoretical preferences adjust away from the extremes of full insurance and no insurance coverage. This prediction not only holds for both coinsurance and deductible contracts, but also can explain the frequently observed preferences for low deductibles in markets for personal insurance.…”
Section: Introductionmentioning
confidence: 99%